Analisis Pemanfaatan E-Learning Walisongo dalam Mata Kuliah Pendidikan Kewarganegaraan - Muna, Na'imatussa'adatul; Khasanah, Milatul; Anbiya, Bakti Fatwa (Research in Education and Technology (REGY), 2023)
Technology is evidence of the times. Technology is a tool to facilitate all access to human life, one of which is in the field of education. With the development of technology, E-learning emerged as one of the innovations of technology products. E-learning is a learning media that utilizes information and communication technology that we can access anywhere and anytime by students. E-learning is also one of the learning media for compulsory civic education courses at the university level. This study aims to find out how the use of e-learning Walisongo in civic education courses, especially at UIN Walisongo Semarang. The type of research used in this study is descriptive qualitative research. Data collection techniques are obtained from two sources, namely primary data in the form of interviews and documentation and secondary data taken from various sources as supporting data from the interview results. The result of this research is that the use of E-learning Waliaongo in civic education courses has gone quite well and is able to have a positive effect on learning even though there are still several obstacles faced by students as seen from the results of interviews and documentation of students of the class of 2021. The advice given by students for E-learning Walisongo is a reinforcement in the process of developing more quality E-learning.